PENGELOLAAN TRACER STUDY DI SMK NEGERI 3 GOWA - Annisa Ramadhani; Wahira, Wahira; Sumarlin Mus (Yayasan Nusantara Hasana Berdikari, 2025)
The implementation of tracer studies is a strategic instrument in ensuring the quality of vocational education. However, the reality on the ground shows that many institutions, including SMKN 3 Gowa, still face serious obstacles such as low alumni participation, difficulty accessing graduate contact data, and the suboptimal use of tracer study results as a basis for curriculum evaluation. This study aims to describe how tracer studies are managed at SMKN 3 Gowa and identify the inhibiting factors that affect their effectiveness. Using a descriptive qualitative approach, this study involved the principal, the head of the Special Job Fair (BKK), and alumni as primary data sources through interviews, observation, and documentation techniques. While secondary data were obtained from school documents and the treservokasi.kemendikbud.go.id application. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that tracer study management at SMKN 3 Gowa has been carried out in a structured manner with the support of digital technology, but is still hampered by limited human resources, low alumni participation, and minimal use of data as a basis for strategic policies. This study concludes that although there is a strong commitment to implementing tracer studies, optimizing tracer study management at SMKN 3 Gowa requires strengthening communication strategies, updating alumni databases, and increasing human resource capacity so that it can function optimally as an instrument for evaluating the quality of vocational education.